Gluteal contour restoration in antiretroviral users and its quality-of-life related impacts: a historical cohort study - Guilherme Barreiro; Fabio Andre Zanella; Karoline Gabriela Dalla Rosa; Adriano Heemann Pereira Neto; Leandro Totti Cavazzola; Pedro Alexandre da Motta Martins (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: Since the introduction of highly active antiretroviral therapy for the treatment of human immunodeficiency virus (HIV), disease mortality has been dramatically reduced worldwide. One related side effect from the use of these drugs is gluteal lipodystrophy. The aim of this study is to assess the quality-of-life impact of correcting this deformity in HIV patients. METHODS: A historical cohort study was conducted between January 2010 and December 2014 with 23 patients, assessing the quality of their lives using the Nottingham Health Profile. A statistical analysis was performed using the McNemar test for related samples. RESULTS: There was a significant difference between preoperative and postoperative response in 19 of the 38 questions. CONCLUSION: We may say that gluteal reconstruction plays a role in improving quality of life for HIV patients who have been affected by antiretroviral related gluteal lipodystrophy.